Les communes bretonnes sur le Web - Hélène Martin-Brelot; Patrick Dieudonné; Jérôme Sawtschuk (Netcom)
In a context of increased uses of Internet and of territorial uncertainty, this study hypothesizes that the Web impacts the spatial dimensions of public organizations, especially by offering a new frame to express various territorial relationships. Exploring the hyperlinks of nearly 400 local authorities websites in Brittany allows estimating the richness of their content (images, videos…) and their openness towards the outside (external links, facebook links…). The thickest websites tend to belong to the biggest cities. However the study of the relationships between these sites shows that very small cities can occupy central locations in the virtual space. We also identify differences in the graphs layouts according to the studied « départements » (Morbihan and Finistère).